0
$\begingroup$

I have constructed truth tables to prove that: $ABC + ABC'+ AB'C +A'BC = AB+AC+BC$

How do I prove it by simplifying the expression? I know that I can simplify: $ABC + ABC' = AB(C+C')=AB$. However I can't repeat this for $AB'C$ or $A'BC$, to get the answer I desire.

I'm fairly new to boolean algebra and have tried to use the basic identities to figure it out, but can't seem to get there.

$\endgroup$
1
$\begingroup$

$ \begin{align} ABC + ABC' + AB'C + A'BC = \\ ABC + ABC + ABC + ABC' + AB'C + A'BC = & & & \text{(2x Idempotency)}\\ AB(C + C') + ABC + ABC + AB'C + A'BC = & & &\text{(Distribution)}\\ AB + ABC + ABC + AB'C + A'BC = & & & \text{(Negation)}\\ AB + (AB + AB')C + (AB + A'B)C = & & & \text{(2x Distribution)} \\ AB + (A(B+B'))C + ((A+A')B)C = & & & \text {(2x Distribution)} \\ AB + AC + BC & & & \text{(2x Negation)} \end{align} $

I'm not proficient at this kind of derivations so please correct any notation/terminology

$\endgroup$
0
$\begingroup$

Idempotency: ABC = ABC + ABC.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.